Electro-thermo-mechanical properties of quasi-isotropic strand in thermal disturbance. (28th June 2021) - Zhang, Guangyi; Wang, Yinshun; Wang, Yueyin; Chen, Yuheng; Zhu, Lingfeng
Abstract: This paper studies the influence of the thermal disturbance process on the electro-thermo-mechanical properties of quasi-isotropic strand (Q-IS) in self-field. We first measured the heat transfer time as well as the longitudinal temperature distribution through experiments and compared them with simulated results. Subsequently, through the finite element analysis, the transversal distribution of the temperature in the center of the strand and the attenuation of the critical current during the thermal disturbance are obtained. Finally, with considering the uniformity of the temperature distribution, the internal stress of the strand under different operating currents was studied. The results show that compared to the strand formed by directly stacked tapes, the Q-IS has advantages of uniform temperature distribution, less attenuation of critical current, and lower amplitude of internal stress in the case of higher current.